2010
DOI: 10.2341/10-064-c
|View full text |Cite
|
Sign up to set email alerts
|

Three-year Clinical Evaluation of Cuspal Coverage with Combined Composite–Amalgam in Endodontically-treated Maxillary Premolars

Abstract: This clinical study evaluated the clinical performance of cuspal coverage with combined composite-amalgam restorations in endodonticallytreated maxillary premolars over a three-year period. Thirty-six maxillary premolars, each with a Class II cavity in 36 patients ranging in age between 28 and 52 years, were selected after endodontic treatment. After reduction of the buccal and palatal cusps, internal coverage and veneering of the reduced buccal cusp was performed with composite. The remaining cavity and reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…The present study showed 20% margin discolorations. This data is consistent with the literature . This may be explained by natural pigmentation of the composite over time.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study showed 20% margin discolorations. This data is consistent with the literature . This may be explained by natural pigmentation of the composite over time.…”
Section: Discussionsupporting
confidence: 93%
“…The best scientific evidence shows that prognosis of an endodontically treated tooth not only depends on endodontic variables, but also on correct tooth rehabilitation . To the best of the authors’ knowledge, there are only two in vivo studies on a critical issue such as the one explored in this investigation. The difficulty in performing a proper follow‐up and standardizing the study are cited as possible reasons for the lack of literature on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…29 A retrospective clinical assessment of 12 combined restorations in extended class II cavities of vital maxillary posterior teeth reported that the composite-amalgam interface in all restorations seemed to be clinically acceptable, even in a sixyear-old restoration.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining cavity and the reduced palatal cusp are restored with amalgam. 29 However, fracture resistance with this technique and with amalgam applied beneath the direct composite coverage is unclear. One study reported that applying amalgam under the composite to restore nonvital maxillary premolars with an MOD cavity without coverage increased resistance to fracture in the treated tooth up to 51% compared to teeth restored with amalgam alone.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, recent studies have concluded that the combined amalgam-composite cusp coverage restoration showed acceptable clinical performance over a period of time [12,13]. Yet, amalgam continues to be the best bargain in the restorative armamentarium because of its durability and technique insensitivity.…”
Section: Discussionmentioning
confidence: 99%